2017
DOI: 10.1007/s11250-017-1401-x
|View full text |Cite
|
Sign up to set email alerts
|

An Ibero-American inter-laboratory trial to evaluate serological tests for the detection of anti-Neospora caninum antibodies in cattle

Abstract: We carried out an inter-laboratory trial to compare the serological tests commonly used for the detection of specific Neospora caninum antibodies in cattle in Ibero-American countries. A total of eight laboratories participated from the following countries: Argentina (n = 4), Brazil (n = 1), Peru (n = 1), Mexico (n = 1), and Spain (n = 1). A blind panel of well-characterized cattle sera (n = 143) and sera representative of the target population (n = 351) was tested by seven in-house indirect fluorescent antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
6
0
6
Order By: Relevance
“…Regarding seroepidemiological studies in dairy cattle carried out in the Amazon region, the prevalence found in this research was higher than the results found by Minervino et al (2008) in Pará (17.5%; cut-off 1:50); Aguiar et al (2006) in Rondônia (11.2%; cut-off 1:25); Boas et al (2015) in Rondônia (10.2%; cut-off 1:100); and similar to those described by Benetti et al (2009) in Mato Grosso (53.5%; cut-off 1:200). However, these values are not entirely comparable since different cut-offs were applied and IFAT reading is partially subjective (Álvarez-García et al, 2003;Campero et al, 2018;Von Blumröder et al, 2004;Wapenaar et al, 2007) We observed that N. caninum is widely spread in the studied region, with only two farms obtaining negative results; however, we could not exclude the presence of this protozoan in these properties due to the number of samples collected.…”
Section: Discussionmentioning
confidence: 77%
“…Regarding seroepidemiological studies in dairy cattle carried out in the Amazon region, the prevalence found in this research was higher than the results found by Minervino et al (2008) in Pará (17.5%; cut-off 1:50); Aguiar et al (2006) in Rondônia (11.2%; cut-off 1:25); Boas et al (2015) in Rondônia (10.2%; cut-off 1:100); and similar to those described by Benetti et al (2009) in Mato Grosso (53.5%; cut-off 1:200). However, these values are not entirely comparable since different cut-offs were applied and IFAT reading is partially subjective (Álvarez-García et al, 2003;Campero et al, 2018;Von Blumröder et al, 2004;Wapenaar et al, 2007) We observed that N. caninum is widely spread in the studied region, with only two farms obtaining negative results; however, we could not exclude the presence of this protozoan in these properties due to the number of samples collected.…”
Section: Discussionmentioning
confidence: 77%
“…Most serologic assays, such as IFAT and ELISA variants, use whole or lysed tachyzoites of N. caninum. 2,12 Although these assays allow the differentiation of infected from uninfected cattle, all of them have some degree of inherent limitation in sensitivity and specificity. The cytoplasmic antigens of the parasite included in the lysates can lead to cross-reactions with other related parasites ( Sarcocystidae family); 19 therefore, greater dilution (1:100 or 1:200) of the serum is required.…”
Section: Discussionmentioning
confidence: 99%
“…The negative control serum (C–) was obtained from a steer considered uninfected after 3 serum samplings taken at 30-d intervals, analyzed by IFAT and iELISA. 12 The same steer was then inoculated intravenously with 1 dose of 10 8 live tachyzoites of N. caninum . The weak positive control (C+) and the strong positive control (C++) sera were obtained after bleeding the steer 21 and 42 d after inoculation, respectively; sera were stored in aliquots at −20°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Mediante análisis ROC se determinó una Dse de 97 % y una Des de 96 %. Este ELISAi mostró buen desempeño en un análisis interlaboratorios iberoamericanos realizado en conjunto con otras pruebas (Campero et al, 2018b).…”
Section: Pruebas Serológicas De Diseño Local (In-house)unclassified